Kinetics and evolved gas analysis for pyrolysis of food processing wastes using TGA/MS/FT-IR. (June 2017) - Özsin, Gamzenur; Pütün, Ayşe Eren
Graphical abstract: Highlights: Pyrolytic decomposition behaviors of three different food processing wastes were studied. Iso-conversional kinetic methods were applied to TGA data. Activation energies of pyrolysis processes were elaborated with respect to conversion degree. Complex reaction schemes during pyrolysis were noticed. Evolved gases were explored by FT-IR and MS spectra. Abstract: The objective of this study was to identify the pyrolysis of different bio-waste produced by food processing industry in a comprehensible manner. For this purpose, pyrolysis behaviors of chestnut shells (CNS), cherry stones (CS) and grape seeds (GS) were investigated by thermogravimetric analysis (TGA) combined with a Fourier-transform infrared (FT-IR) spectrometer and a mass spectrometer (MS). In order to make available theoretical groundwork for biomass pyrolysis, activation energies were calculated with the help of four different model-free kinetic methods. The results are attributed to the complex reaction schemes which imply parallel, competitive and complex reactions during pyrolysis. During pyrolysis, the evolution of volatiles was also characterized by FT-IR and MS. The main evolved gases were determined as H2 O, CO2 and hydrocarbons such as CH4 and temperature dependent profiles of the species were obtained.